Detection of clinically important β-lactamases by using PCR - Mlynarcik, Patrik; Dolejska, Monika; Vagnerova, Iva; Kutilová, Iva; Kolar, Milan (FEMS microbiology letters, 2021)
Increasing antimicrobial resistance of nosocomial pathogens is becoming a serious threat to public health. To control the spread of this resistance, it is necessary to detect β-lactamase-producing organisms in the clinical setting. The aims of the study were to design a PCR assay for rapid detection of clinically encountered β-lactamase genes described in Enterobacteriaceae and Gram-negative non-fermenting bacteria. The functionality of proposed primers was verified using eight reference strains and 17 strains from our collection, which contained 29 different β-lactamase genes. PCR products of the test strains were confirmed by Sanger sequencing. Sequence analysis was performed using bioinformatics software Geneious. Overall, 67 pairs of primers for detecting 12 members of the class C β-lactamase family, 15 members of class A β-lactamases, six gene families of subclass B1, one member each of subclasses B2, B3 and class D β-lactamases were designed, of which 43 pairs were experimentally tested in vitro. All 29 β-lactamase genes, including 10 oxacillinase subgroups, were correctly identified by PCR. The proposed set of primers should be able to specifically detect 99.7% of analyzed β-lactamase subtypes and more than 79.8% of all described β-lactamase genes.
Keywords: β-lactamase; polymerázová řetězová reakce; beta-laktamasy; Polymerase Chain Reaction; DNA bakterií; bakteriologické techniky; Bacteriological Techniques; DNA, Bacterial; lidé; DNA primery; beta-laktamová rezistence; beta-Lactamases; PCR; primer; beta-Lactam Resistance; Bacteria; DNA Primers; antibiotic resistance; bacteria; Humans